Frequency Distribution of Apoprotein(a) Isoforms in Patients with Diabetes Mellitus and Healthy Subjects - Labudovic D; Toseska, KN; Alabakovska, BS; Dimitrovski, C; Jurhar, M; Isjanovska, R; Spiroski, M; Todorovska BB (My University, 2003)
Aim. To determine the frequency distribution of apoprotein(a) isoforms in patientswith insulin-dependent (IDDM) and non-insulin-dependent (NIDDM) diabetes mellitus and healthy subjects. Method.We separated and visualized 5 apo(a) isoforms in 40 patients with IDDM (12men aged 48.00±4.59 and 28 women aged 52.37±8.21), 65 patients with NIDDM (26 men aged 61.88±9.25 and 39 women aged 60.15±7.98), and 182 healthy subjects, using 3-15% gradient sodium dodecyl sulfate polyacrylamide gel electrophoresis, followed by immunoblotting. Results. The frequency distribution of apo(a) isoforms was very similar in patientswith diabetes mellitus and the control group. Atherogenic lowmolecular weight (LMW) S1 apo(a) isoform was more frequent in patients with IDDM (7.5%) and NIDDM (6.15%) than in the control group (0.78%). LMW S1 apo(a) isoform in patients with IDDM (relative risk [RR], 6.86; 95% confidence interval [CI], 1.19-25.21; p<0.001) and patients with NIDDM (RR, 7.04; 95% CI, 1.40-35.40; p=0.0057) as well as high molecularweight>S4 apo(a) isoform in patientswithNIDDM(RR, 2.39; 95% CI, 1.28-5.21; p=0.0067) significantly increased the risk for the development of atherosclerosis. Mean molecular weight of S3, S1, and B apo(a) isoforms was higher in patientswithIDDMandNIDDMthan in the healthy subjects carriers of the same isoforms, but this differencewas not statistically significant.Weestimated high inverse statistical correlation between apo(a) size (kDa) and plasma lipoprotein(a) concentration in all study groups, patients with IDDM (p<0.001), patients with NIDDM (p<0.001), and healthy subjects (p<0.01). Conclusion. Not only the increased plasma Lp(a) levels, but also apoprotein(a) isoforms may play an important role as a risk factor for the development of atherosclerosis in patients with diabetes mellitus.